(untitled) (Muitas Vozes, 2022)
From the notion of “microsociology” and “institutional rites” proposed by Brown and Levinson (1987) and considering a pragmatic perspective widely explored in Linguistics, this article aims to examine the “justice in action” (MARTÍNEZ, 2007; DUPRET), in line with one of the principles of the perspective of interactional studies, which seek to understand “language in action” (TRAVERSO). Such methodology with ethnomethodological inspiration aims, finally, the analysis of oral texts that result from situations of verbal exchange, in contexts of face to face contact, “produced by more than one person in interaction” (SCHEGLOFF, 1996). In this way, what was previously considered the “garbage can” of linguistics will gain the status of luxury here, thanks to the contribution of ethnomethodological studies dating back to the second half of the 20th century. From the case study presented here (the case of income taxes), based on the analysis of the talking-in-interaction (KERBRAT-ORECHIONNI, 2011), we will realize, after all, that a sentence is the result of of values, life experience, norms and legal principles, which, together, act as a form of device capable of leading a law enforcement officer (here represented by three magistrates in the second degree of jurisdiction) to change (recategorize) a decision already taken by judges